2010
DOI: 10.4314/br.v7i2.56580
|View full text |Cite
|
Sign up to set email alerts
|

Changes in alt, ast and alp values of plasma and serum samples stored at refrigerator (4 0c) and room temperature (32 0c) for up to five days

Abstract: This study investigated the time-related changes in the alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP) values of serum and plasma samples stored at refrigerator (2 -8 o C, average of 40 C) and room temperature (30-34 0 C, average of 32 0 C) for a period of 120 hours (5 days). Blood samples were obtained from a total of 20 patients that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(15 reference statements)
0
1
1
1
Order By: Relevance
“…ALT results as well indicated that reliable results can be obtained on serum stored at room temperature and analysed within 24 hours. This was however in contradiction to the findings by Nwosu et al (2009) who determined that reliable ALT results can only be obtained when the analysis is done within 16 hours of sample collection if left at room temperature. AST also gave reliable results until the 24 th -hour analysis in this study.…”
Section: Concentration Changes and The Stability Of The Selected Bioc...contrasting
confidence: 87%
See 1 more Smart Citation
“…ALT results as well indicated that reliable results can be obtained on serum stored at room temperature and analysed within 24 hours. This was however in contradiction to the findings by Nwosu et al (2009) who determined that reliable ALT results can only be obtained when the analysis is done within 16 hours of sample collection if left at room temperature. AST also gave reliable results until the 24 th -hour analysis in this study.…”
Section: Concentration Changes and The Stability Of The Selected Bioc...contrasting
confidence: 87%
“…AST also gave reliable results until the 24 th -hour analysis in this study. Nwosu et al (2009) however found that reliable AST values without adverse clinical impact could only be obtained when analyses were done within 10 hours from sample collection. Such differences can be accounted for by population (liver disease patients vs healthy volunteers) and environmental differences.…”
Section: Concentration Changes and The Stability Of The Selected Bioc...mentioning
confidence: 97%
“…Juul (1967) reportou o aumento da concentração de TGO e TGP a partir de 1 dia da coleta de amostras de soro humano quando estas são mantidas a temperatura ambiente. Já de acordo com Nwosu et al (2009), amostras refrigeradas de soro e plasma humanos apresentaram concentrações de TGO e TGP estáveis em até 30 horas se refrigeradas a 4 ºC ou em até 8 horas a temperatura ambiente. Divya e Jayavardhanan (2011) avaliaram amostras de soro de búfalos e reportaram que a concentração de TGP é estável sob refrigeração a 4 ºC por um período de 14 dias, mas instável a temperatura ambiente, apresentando diminuição contínua da concentração, enquanto TGP apresentou concentração estável por 11 dias sob refrigeração a 4 ºC e por 8 dias em temperatura ambiente.…”
Section: Intervalo De Concentração Do Controleunclassified